Comparative analysis of DNA extraction methods to study the body surface microbiota of insects: A case study with ant cuticular bacteria. (21st June 2017) - Birer, Caroline; Tysklind, Niklas; Zinger, Lucie; Duplais, Christophe
Abstract: High‐throughput sequencing of the 16S rRNA gene has considerably helped revealing the essential role of bacteria living on insect cuticles in the ecophysiology and behaviour of their hosts. However, our understanding of host‐cuticular microbiota feedbacks remains hampered by the difficulties of working with low bacterial DNA quantities as with individual insect cuticle samples, which are more prone to molecular biases and contaminations. Herein, we conducted a methodological benchmark on the cuticular bacterial loads retrieved from two Neotropical ant species of different body size and ecology: Atta cephalotes (~15 mm) and Pseudomyrmex penetrator (~5 mm). We evaluated the richness and composition of the cuticular microbiota, as well as the amount of biases and contamination produced by four DNA extraction protocols. We also addressed how bacterial community characteristics would be affected by the number of individuals or individual body size used for DNA extraction. Most extraction methods yielded similar results in terms of bacterial diversity and composition for A. cephalotes (~15 mm). In contrast, greater amounts of artefactual sequences and contaminations, as well as noticeable differences in bacterial community characteristics were observed between extraction methods for P. penetrator (~5 mm). We also found that large (~15 mm) and small (~5 mm) A. cephalotes individuals harbour different bacterial communities. Our benchmark suggests that cuticular microbiota of single individual insects can be reliably retrieved provided that blank controls, appropriate data cleaning, and individual body size and functional role within insect society are considered in the experiment.